Nevus Lipomatosus Superficialis on the Left Proximal Arm - Alexander K. C. Leung; Benjamin Barankin (Hindawi Limited, 2017)
We report a 58-year-old woman with a solitary type of nevus lipomatosus superficialis on the left proximal arm. To our knowledge, the occurrence of a solitary type of nevus lipomatosus superficialis on the arm has very rarely been reported. A perusal of the literature revealed but one case, to which we are going to add another one. Recognition of this clinical manifestation is important so that a proper diagnosis can be made.